Textiles sustainability and communications - Carp, Belinda (Array, 2020)
The Industrial Revolution paved the way for industrialisation, economic growth and innovation, and resulted in the availability of an increased range of goods and services, improved life expectancy, and many other benefits. However, the rapid development has come at a cost which has not yet been settled. The earth’s natural resources are being used at a rate that cannot be sustained by the natural ecosystem and, according to the Chief Scientific Adviser to the UK government in 2009, we are heading for a "perfect storm" where a growing world population will demand yet more resources from an earth which simply cannot sustain demand.